A Review of Medicinal Plants with Antiviral Activity Available in Bangladesh and Mechanistic Insight Into Their Bioactive Metabolites on SARS-CoV-2, HIV and HBV - Sitesh C. Bachar; Kishor Mazumder; Kishor Mazumder; Kishor Mazumder; Ritesh Bachar; Asma Aktar; Mamun Al Mahtab (Frontiers Media S.A., 2021)
Currently, viral infection is the most serious health issue which causing unexpected higher rate of death globally. Many viruses are not yet curable, such as corona virus-2 (SARS-CoV-2), human immunodeficiency virus (HIV), hepatitis virus, human papilloma virus and so others. Furthermore, the toxicities and ineffective responses to resistant strains of synthetic antiviral drugs have reinforced the search of effective and alternative treatment options, such as plant-derived antiviral drug molecules. Therefore, in the present review, an attempt has been taken to summarize the medicinal plants reported for exhibiting antiviral activities available in Bangladesh along with discussing the mechanistic insights into their bioactive components against three most hazardous viruses, namely SARS-CoV-2, HIV, and HBV. The review covers 46 medicinal plants with antiviral activity from 25 families. Among the reported 79 bioactive compounds having antiviral activities isolated from these plants, about 37 of them have been reported for significant activities against varieties of viruses. Hesperidin, apigenin, luteolin, seselin, 6-gingerol, humulene epoxide, quercetin, kaempferol, curcumin, and epigallocatechin-3-gallate (EGCG) have been reported to inhibit multiple molecular targets of SARS-CoV-2 viral replication in a number of in silico investigations. Besides, numerous in silico, in vitro, and in vivo bioassays have been demonstrated that EGCG, anolignan-A, and B, ajoene, curcumin, and oleanolic acid exhibit anti-HIV activity while piperine, ursolic acid, oleanolic acid, (+)-cycloolivil-4'-O-β-d-glucopyranoside, quercetin, EGCG, kaempferol, aloin, apigenin, rosmarinic acid, andrographolide, and hesperidin possess anti-HBV activity. Thus, the antiviral medicinal plants and the isolated bioactive compounds may be considered for further advanced investigations with the aim of the development of effective and affordable antiviral drugs.